The volatile oils of Euodia hortensis forma hortensis - Brophy, Joseph J.; Rahmani, Mawardi; Toia, Robert F.; Croft, Kevin D.; Lassak, Erich V. (John Wiley & Sons, 1985)
The volatile leaf oil of Euodia hortensis forma hortensis contains menthofuran (64%) and evodone (27%) as its major components. Another forty-two components have been detected in the oil of which twenty-nine have been identified. The volatile oil from the flowers contains evodone as its main component with lesser amounts of menthofuran, α-copaene, ar-curcumene and caryophyllene